2020
DOI: 10.5194/acp-20-15265-2020
|View full text |Cite
|
Sign up to set email alerts
|

The dual-field-of-view polarization lidar technique: a new concept in monitoring aerosol effects in liquid-water clouds – case studies

Abstract: Abstract. In a companion article (Jimenez et al., 2020), we introduced a new lidar method to derive microphysical properties of liquid-water clouds (cloud extinction coefficient, droplet effective radius, liquid-water content, cloud droplet number concentration Nd) at a height of 50–100 m above the cloud base together with aerosol information (aerosol extinction coefficients, cloud condensation nuclei concentration NCCN) below the cloud layer so that detailed studies of the influence of given aerosol condition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Once in the UTLS height range, smoke particles become quickly distributed over large parts of the Northern Hemisphere within a few weeks, as observed and documented for the first time in 2001 (Fromm et al, 2008) and recently confirmed after the record-breaking Canadian fires in the summer of 2017 (Khaykin et al, 2018;Baars et al, 2019). In the case of the strong Siberian fires, the smoke particles probably became quickly distributed over the entire Arctic region (as suggested by the satellite observations presented by Johnson et al, 2021) and then remained in the UTLS height range for months. The decay of smoke-related stratospheric perturbations usually takes more than a half year (Baars et al, 2019).…”
Section: Wildfire Smoke Layer In the Utls Regimesupporting
confidence: 55%
See 1 more Smart Citation
“…Once in the UTLS height range, smoke particles become quickly distributed over large parts of the Northern Hemisphere within a few weeks, as observed and documented for the first time in 2001 (Fromm et al, 2008) and recently confirmed after the record-breaking Canadian fires in the summer of 2017 (Khaykin et al, 2018;Baars et al, 2019). In the case of the strong Siberian fires, the smoke particles probably became quickly distributed over the entire Arctic region (as suggested by the satellite observations presented by Johnson et al, 2021) and then remained in the UTLS height range for months. The decay of smoke-related stratospheric perturbations usually takes more than a half year (Baars et al, 2019).…”
Section: Wildfire Smoke Layer In the Utls Regimesupporting
confidence: 55%
“…Extreme and long-lasting wildfires in central and eastern Siberia, in closest neighborhood to the Arctic region, were most probably responsible for the UTLS smoke layer over the High Arctic in the winter half year of -2020(Johnson et al, 2021Ohneiser et al, 2021). The main burning phase lasted from 19 July to 14 August 2019.…”
Section: Wildfire Smoke Layer In the Utls Regimementioning
confidence: 99%
“…Two telescopes (receiver sub-units) permit near-field and far-field observations. The co-polarized signal components, required to determine profiles of depolarization ratios, are obtained from the difference of the total minus the cross-polarized signal component (after careful correction of all instrumental influences on the signals) (Engelmann et al, 2016;Jimenez et al, 2020).…”
Section: Caliop Vs Polly: Different Aerosol Typing Optionsmentioning
confidence: 99%
“…Hence, the free tropospheric aerosol is predominantly of marine origin with low concentrations overall. First results of the DACAPO-PESO campaign regarding events of significant aerosol load (Ohneiser et al, 2020;Floutsi et al, 2021), liquid cloud microphysics (Jimenez et al, 2020) and integrated water vapor observations (Bromwich et al, 2020) are already published. Observations at Leipzig were performed before October 2016 and between the deployments to Limassol and Punta Arenas.…”
Section: Introductionmentioning
confidence: 99%